2019
DOI: 10.1080/19420889.2019.1625661
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Defense Theory 2.0: tissue-specific stress defense prioritization as an extra layer of complexity

Abstract: In nature, plants need to be able to quickly adapt to changing environments during their lifetime in order to maintain fitness. Different defense responses are not only costly, but often also antagonistic to one another. Hence, when faced with multiple stresses simultaneously, plants likely have to prioritize their defense responses. This type of crosstalk between different stress response pathways is suggested to balance the high costs of triggering and maintaining stress responses with the limited amount of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…The mechanism of drought tolerance in lsd1 null mutants and ADR1 overexpression lines is thought to involve SA but to be independent of abscisic acid (ABA), consistent with the described antagonism between SA and ABA (Moeder et al, 2010). Recent studies have started to elucidate components mediating this cross-talk and prioritization (Berens et al, 2019;Wolinska and Berens, 2019) and further studies are essential to fully understand how abiotic and biotic stress responses are regulated.…”
Section: Introductionmentioning
confidence: 77%
“…The mechanism of drought tolerance in lsd1 null mutants and ADR1 overexpression lines is thought to involve SA but to be independent of abscisic acid (ABA), consistent with the described antagonism between SA and ABA (Moeder et al, 2010). Recent studies have started to elucidate components mediating this cross-talk and prioritization (Berens et al, 2019;Wolinska and Berens, 2019) and further studies are essential to fully understand how abiotic and biotic stress responses are regulated.…”
Section: Introductionmentioning
confidence: 77%
“…For example, previous research has shown that surface-feeding waterbirds consumed high proportions of macrophyte flowers, but whether this is because the flowers are easier to reach or because the flowers are more palatable is not clear (Wood et al, 2012). Also, according to the ODT, when simultaneously exposed to multiple stress conditions, plants likely prioritize their defensive responses (Wolinska and Berens, 2019). Thus, based on our experimental results, we hypothesize that the floating life-form N. humboldtiana, with its parts simultaneously exposed, invests more of its resources in protecting its most valuable parts (i.e., long stem internodes).…”
Section: Discussionmentioning
confidence: 99%
“…According to ODT, stress responses are prioritized in the most valuable parts (Keith and Mitchell-Olds, 2017), and recent findings indicate that Arabidopsis plants spatially separate contrasting stress responses in leaves of different ages (e.g. young leaves exhibit higher biotic stress responses but lower abiotic stress responses compared with old leaves) (Berens et al , 2019; Wolinska and Berens, 2019). To date, little information is available on the molecular mechanisms by which biotic and abiotic stress responses are differentially prioritized in plants, and how they adapt to conflicting stresses for optimal responses.…”
Section: Introductionmentioning
confidence: 99%
“…At the organismal level, hormone crosstalk might also balance trade-offs between conflicting biotic and abiotic stress responses (i.e. prioritization of responses in leaves of Arabidopsis plants) (Berens et al , 2019; Wolinska and Berens, 2019). Sugar and ROS have also been proposed as candidates signaling molecules to regulate prioritization between biotic and abiotic stress responses (Wolinska and Berens, 2019).…”
Section: Introductionmentioning
confidence: 99%